2013
DOI: 10.1007/s00784-013-1064-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of cone beam computed tomography to predetermine root canal lengths in molar teeth: a comparison between two-dimensional and three-dimensional measurements

Abstract: In cases where a CBCT is already available, root canal lengths in molar teeth can be accurately predetermined using a standardized 3D approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
6
11
1
Order By: Relevance
“…A study in the white population 2 showed that all analyzed molars had two roots, as presented in the study we conducted. Similar results were found in studies conducted in Spain 24 , and Belgium and Chile 27 , while studies conducted in Korea 5 and Thailand 28 showed a lower percentage of two roots (87.3% and 73.5%, respectively).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…A study in the white population 2 showed that all analyzed molars had two roots, as presented in the study we conducted. Similar results were found in studies conducted in Spain 24 , and Belgium and Chile 27 , while studies conducted in Korea 5 and Thailand 28 showed a lower percentage of two roots (87.3% and 73.5%, respectively).…”
Section: Discussionsupporting
confidence: 87%
“…Vertucci type I was the most frequent, which coincides with the results of studies conducted in Spain and Belgium 24,27 . Vertucci types II and III were found in a low percentage, as in other studies 5,24,29 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations